Reform and Reconstruction of Law No. 20 of 2003 on The National Education System Toward A New Paradigm for National Education - Thomas Suyatno; Suparno Suparno (Jurnal Sosial Teknologi, 2026)
This study aims to analyze the need for reform and reconstruction of Law Number 20 of 2003 concerning the National Education System in order to realize a new paradigm of national education that is adaptive to current developments. This research is motivated by the gap between the legal norms in the 1945 Constitution of the Republic of Indonesia and the implementation of education in the field. The method used is a qualitative approach with a normative juridical research type combined with a socio-legal approach through literature study. The results of the study indicate that the national education system still faces various problems, such as inequality in access to and quality of education, suboptimal budget management, discrimination between public and private educational institutions, and a dichotomy between general and religious education. Furthermore, existing regulations are deemed unable to accommodate the principles of modern education that are inclusive, flexible, and oriented toward lifelong learning, especially in facing the era of digital transformation and artificial intelligence. Therefore, reform and reconstruction of the national education system are needed through regulatory updates, strengthening governance, and changing the educational paradigm to be oriented toward developing 21st-century competencies. This research is expected to contribute to the development of a more responsive and sustainable national education policy.